Interpreting films : studies in the historical reception of American cinema - Staiger, Janet (Princeton, N.J. : Princeton University Press, 1992)
Employing a wide range of examples from Uncle Tom's Cabin and Birth of a Nation to Zelig and Personal Best, Janet Staiger argues that a historical examination of spectators' responses to films can make a valuable contribution to the history, criticism, and philosophy of cultural products. She maintains that as artifacts, films do not contain immanent meanings, that differences among interpretations have historical bases, and that these variations are due to social.
Political, and economic conditions as well as the viewers' constructed images of themselves. Alter proposing a theory of reception study, the author demonstrates its application mainly through analyzing the varying responses of audiences to certain films at specific moments in history. Staiger gives special attention to how questions of class, gender, sexual preference, race, and ethnicity enter into film viewers' interpretations. Her analysis reflects recent.
Developments in post-structuralism, cognitive psychology, psychoanalysis, and cultural studies, and includes a discussion of current reader-response models in literary and film studies as well as an alternative approach for thinking about historical readers and spectators.
The use-value of reception studies -- Reception studies in other disciplines -- Reception studies in film and television -- Toward a historical materialist approach to reception studies -- Rethinking "primitive" cinema: intertextuality, the middle-class audience, and reception studies -- "The handmaiden of villainy": foolish wives, politics, gender orientation, and the other -- The birth of a nation: reconsidering its reception -- The logic of alternative readings: a star is born -- With the compliments of the auteur: art cinema and the complexities of its reading strategies -- Chameleon in the film, chameleons in the audience; or, where is parody? the case of zelig.
Includes bibliographical references (p. [259]-269) and index.
Description based on print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Motion pictures -- Aesthetics; Reader-response criticism; Motion pictures -- United States; Cinéma -- Esthétique.; Esthétique de la réception.; Cinéma -- États-Unis.; PERFORMING ARTS -- Film & Video -- History & Criticism; Motion pictures; Motion pictures -- Aesthetics; Reader-response criticism; United States; Films; Receptie; Cinema -- Films (Motion pictures) -- History; United States